Thermal Glass Stress Analysis – Design Considerations - Michaela Poláková (Challenging Glass Conference, 2018)
The use of glass in windows and curtain walls, in residential as well as in high-rise buildings, is something that requires great care in design and execution. Apart from complying with typical structural engineering practices and ensuring, for example, that the glass thickness is sufficient to withstand wind loads, impact loads etc. it is necessary always also to consider the thermal-stress resistance of the glass employed as well as the temperature distribution across glass and façade components. This topic is not new as it began to be analysed with the emergence of the first body tinted basic glass types. All the analysis done today is based on a linear approach and a more or less simplified algorithm. But modern constructions make it necessary to recognize special details and to acquire a more detailed view of the construction and use of such windows and curtain walls. Glass manufacturers can assist in this by helping to analyse the thermal stress characteristics but also the temperature distribution in different constructions. It is necessary here also to evaluate the different boundary conditions, which vary from location to location. The paper will begin by describing the basic methods for analysing the thermal-stress resistance of glazing units. But it will then go on to show the influence of the boundary conditions on the final result. The paper will also show the effect of a detailed 2D FE analysis in specifically analysing critical locations in curtain walls, such as shadow boxes or spandrel areas.